2022
DOI: 10.3389/fmicb.2022.811673
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Autophagy Are Important Processes in Post Ripeness and Brown Film Formation in Mycelium of Lentinula edodes

Abstract: Lentinula edodes (Berk.) Pegler, the shiitake mushroom, is one of the most important mushrooms in the global mushroom industry. Although mycelium post ripeness and brown film (BF) formation are crucial for fruiting body initiation, the underlying molecular mechanisms of BF formation are largely unknown. In this study, proteomic quantification (relative and absolute) and metabolomic profiling of L. edodes were performed using isobaric tags and gas chromatography-mass spectroscopy, respectively. A total of 2,474… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…Although no autophagy-related KEGG pathway was enriched in the red-stipe symptom morel DAMs, certain metabolites were associated with autophagy, including mannitol (neg-1.083_182.07879 and neg-0.884_182.07874) and glutamine (pos-0.85_146.06874, pos-3.284_146.06897, pos-1.024_146.06877, neg-1.007_146.06889, and neg-0.821_146.06887). Thus, these metabolites are potentially associated with the red-stipe symptom of morels, which is consistent with a previous report that identified that autophagy was important in post ripeness and brown film formation in Lentinula edodes [ 71 ]. To maintain cell integrity, the cell wall serves as the primary barrier against the external environment [ 72 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although no autophagy-related KEGG pathway was enriched in the red-stipe symptom morel DAMs, certain metabolites were associated with autophagy, including mannitol (neg-1.083_182.07879 and neg-0.884_182.07874) and glutamine (pos-0.85_146.06874, pos-3.284_146.06897, pos-1.024_146.06877, neg-1.007_146.06889, and neg-0.821_146.06887). Thus, these metabolites are potentially associated with the red-stipe symptom of morels, which is consistent with a previous report that identified that autophagy was important in post ripeness and brown film formation in Lentinula edodes [ 71 ]. To maintain cell integrity, the cell wall serves as the primary barrier against the external environment [ 72 ].…”
Section: Discussionsupporting
confidence: 92%
“…LeRPD3, a homologue of Rpd3 of histone deacetylase complex in L. edodes, was 1.63-fold overexpressed in the present study (Figure 2), indicating the regulation of mitophagy through protein kinase TORC1. Similarly, it was also previously suggested that LeRPD3 and LeTORC1 are involved in oxidative stress and autophagy of the L. edodes brown film formation process through proteomic quantification analysis [15]. Different from TOR signalling, the MAPK signalling pathway regulates mitophagy but not non-selective autophagy [41].…”
Section: Discussionmentioning
confidence: 89%
“…At the transcriptome level, there are various differentially expressed genes of autophagy and age-dependent response in L. edodes mycelia and fruiting bodies postpigmentation [11][12][13]. At the proteome level, the expression of autophagy key factor vacuolar protein sorting (VPS1, VPS27, and VPS34) vacuolar membrane protein (VAC8) is significantly increased in L. edodes pigment mycelium [14,15]. At the metabolomics level, the differential metabolites-asparagine, proline, leucine, valine, glutamine, and palmitic acid-are related to autophagy, apoptosis, and reactive oxygen species (ROS)-mediated oxidative stress [16].…”
Section: Introductionmentioning
confidence: 99%
“…7B ). Thus, BF formation is associated with melanin deposition in the cell wall and generation of vacuoles, and the latter may be related to autophagy ( 17 ). The ubiquitin-like protein ATG8 forms an expanding structure with phosphatidyl ethanolamine (PE) to regulate autophagosome formation ( 20 , 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous proteomics study, we found that the deacetylase RPD3 was significantly upregulated during mycelial BF formation and postripening in L. edodes ( 17 ). In addition, a growing body of evidence showed that acetylation can regulate autophagy ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 90%